Priority of Kaplan Turbine and Small Hydropower Plants Over Other Resources: An Overview - Hammid, Ali Thaeer; M. H., Sulaiman; Kadhim, Atheer A.; Kareem, Ali N.; Jadaa, Khalid J. (Medwell Journals, 2017)
Many developed countries gradually begin to dispense traditional energy origins plants that built on oil, coal usual gas owing to oil prices increment, fossil fuel cost, thermal pollution, and the crisis of worldwide energy. Large hydropower plants (LHP) and Mini (MHP) are less feasible than a small hydropower plant (SHP). Up to now, the Mechanism of appropriated turbine selection for a specific purpose is undefined obviously. Classification of hydropower schemes generally depends on the capacity of production. An installed plant capacity of up to 25 MW is regarded as an SHP. The capability of the SHP and future production and its economic operating option like run-of-river and clean development mechanism (CDM) making it's desirable. Moreover, in order to achieve dependable and reasonable production. Turbines classification divided according to turbines' net head and flow water rate. In this article, we provide analyzing and surveying on categories of the hydropower plant to show characteristics of each one, different SHP technology, properties for appropriated turbine and evaluate the economic potential of the feasible power plant.